Prenatal sonographic diagnosis of Holt-Oram syndrome - Tongsong T. (2014)
Holt-Oram syndrome is an autosomal dominant disorder characterized by heart defects in combination with characteristic upper-limb abnormalities. A woman with no family history of genetic diseases underwent prenatal sonography at 25 weeks' menstrual age to screen for fetal anomalies. Sonography revealed abnormalities in the upper limbs and heart. The limb abnormalities included bilateral absence of radii and thumbs: the left hand had no carpal or metacarpal bones, and each of the 4 fingers on that hand had only 1 phalangeal bone. Cardiac malformations included an atrial septal defect and Ebstein's anomaly. Other structures were normal. Prenatal cytogenetic analysis by cordocentesis revealed a normal 46,XY karyotype. Spontaneous labor and delivery at 34 weeks' menstrual age produced a 1,960-g male infant who died of cardiac insufficiency shortly after birth. The postnatal appearance and autopsy findings confirmed the prenatal findings. In this case, Holt-Oram syndrome was readily diagnosed by prenatal sonography.